The correspondence of Dante Gabriel Rossetti : the formative years, 1835-1862. edited by William E. Fredeman. - Rossetti, Dante Gabriel, 1828-1882 (Boydell & Brewer., 2002)
This nine-volume edition represents the definitive collection of extant Rossetti correspondence, an outstanding primary witness to the range of ideas and opinions that shaped Rossetti's art and poetry.